Early Prenatal Diagnosis of Ectopia Cordis: A Case Report - Esinler, Deniz; Yırtıcı, Bülent; Yalvaç, Serdar; Esin, Sertaç; Kandemir, Ömer (Gynecology Obstetrics & Reproductive Medicine, 2014)
Ectopia cordis is a very rare congenital anomaly with an incidence of 5.5-7.9 per million live births. In this manuscript we report an ectopia cordis diagnosed in a fetus at 12 weeks.